Financial incentives for achieving and maintaining viral suppression among HIV-positive adults in Uganda: a randomised controlled trial. Issue 3 (March 2019) - Thirumurthy, Harsha; Ndyabakira, Alex; Marson, Kara; Emperador, Devy; Kamya, Moses; Havlir, Diane; Kwarisiima, Dalsone; Chamie, Gabriel
Summary: Background: Viral suppression among HIV-positive individuals is essential for protecting health and preventing HIV transmission. Financial incentives have shown promise in modifying various health behaviours in low-income countries but few studies have assessed whether they can improve HIV treatment outcomes. We aimed to determine the impact of time-limited financial incentives on viral suppression among HIV-positive adults in rural Uganda. Methods: We did a randomised controlled trial in four rural Ugandan parishes. We recruited HIV-positive individuals (aged ≥18 years) from community health campaigns that included HIV testing services or at a local government health facility where HIV treatment is offered. Participants included those who were initiating antiretroviral therapy (ART) or already receiving ART. Eligibility to participate in the study did not depend on current ART or viral suppression status. Participants were randomly allocated (1:1) to the financial incentive intervention or the control group in computer-generated blocks (block size 10 participants) and pre-printed scratch cards were used to reveal study group assignment. We measured participants' viral load at baseline and at weeks 6, 12, 24, and 48. At each timepoint, we provided results and viral load counselling. Participants in the intervention group received financial incentives for viral suppression at weeks 6, 12, and 24, with incentive amounts increasing from US$4 to $12·5. The primary outcome was viral suppression (viral load <400 copies per mL) at 24 weeks in the intention-to-treat population. This trial is registered withClinicalTrials.gov, numberNCT02890459 . Findings: Between June 27, 2016, and May 25, 2018, we enrolled 400 adults in the study, of whom 203 were randomly assigned to the intervention group and 197 to the control group. Of these, 324 were enrolled from community health campaigns and 76 from the government clinic. Eight (2%) withdrew from the study and were not included in analyses. Over the 48-week follow-up period, 35 (9%) died or were lost-to-follow-up. Participants' median daily income was $0·79. At baseline, 300 participants (77%) were virally suppressed. In intention-to-treat analyses, 168 participants (84%) in the intervention group and 156 (82%) in the control group were virally suppressed at 24 weeks (odds ratio 1·14, 95% CI 0·68–1·93, p=0·62). Six participants (3%) in the control group and four (2%) in the intervention group had adverse events. Six of the adverse events were serious, including two deaths in the intervention group, three deaths in the control group, and one serious injury (tibia fracture) after an auto accident. No adverse events or deaths were related to study participation. Interpretation: Financial incentives had no effect on viral suppression among HIV-positive adults. High baseline viral suppression and provision of viral load results might have contributed to high viral suppression among participants. These findings highlight the need for interventions that promote achievement of viral suppression among unsuppressed individuals. Funding: National Institute of Mental Health at the US National Institutes of Health.